Rhinonyssidae (Acari) in the house sparrows, Passer domesticus (Linnaeus, 1758) (Passeriformes: Passeridae), from southern Brazil - Santos,Luciana Siqueira Silveira dos (2018)
Abstract We report the occurrence and infection parameters of two species of nasal mites in Passer domesticus (Linnaeus, 1758) (house sparrow). Nasal passages, trachea, lungs, and air sacs of 100 house sparrows captured in an urban area at the city of Pelotas, State of Rio Grande do Sul, southern Brazil, were examined with a stereomicroscope. The mite, Sternostoma tracheacolum Lawrence, 1948 was present in the trachea and/or lungs (or both) of 13 birds (13%) at a mean intensity of 6.7 mites/infected host. Ptilonyssus hirsti (Castro & Pereira, 1947) was found in the nasal cavity of 1 sparrow (1%); coinfection was not observed in this bird. There was no significant difference in the prevalence and mean intensity of infection of S. tracheacolum between male and female birds. To our knowledge, this is the first study reporting the occurrence of S. tracheacolum in P. domesticus in Brazil and the presence of P. hirsti in P. domesticus from Rio Grande do Sul, Brazil. This is the first survey to provide the infection parameters of each of these mites in house sparrows.